Strategi Peningkatan Keterampilan Menyimak Teks Aural di Kelas III SD Dengan Bantuan Media Audio Visual - Hazila Rizkina Julvi; Chandra Chandra; Inggria Kharisma (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to improve listening skills to aural texts in grade III elementary school students through the use of audio-visual media. With the presence of audio-visual media, it is hoped that students' motivation and concentration levels during the learning process can increase. This study uses a qualitative descriptive method, with data collection techniques through tests that assess cognitive aspects and non-test methods such as observation and documentation. The use of audio-visual animated films is expected to help students concentrate more and pay full attention to the material being taught. In addition, a fun learning approach is also expected to increase students' interest and enthusiasm in participating in learning activities.